Qualidade fisiológica de diásporos, produção de mudas e desenvolvimento inicial a campo de Balfourodendron riedelianum (engl.) engl. - Gomes, Daniele Rodrigues (2016)
The Balfourodendron riedelianum of the family Rutaceae is a native forest species with timber value and is used in the manufacture of luxury furniture, construction, and so forth. Moreover, the species is suitable for medical use, insecticide, landscaping and recovery riparian areas. Despite the importance of this species, there are few studies in relation to seed technology, irrigation in the production of seedlings and field early growth. In this sense, species diaspores were collected in Palma Nova (RS), in the years of 2013 and 2015, and further processed and divided into samples for testing. The study was divided into three articles, in Article I – measurement of biometrics, pre-germination treatments and substrates for the germination of B. riedelianum diaspores; by using a sample of 2013 for physical characterization, through the weight of a thousand seeds (PMS), water content (TU) and biometrics, besides the germination test (G%) on different substrates after breaking dormancy. The dimensions of the B. riedelianum seeds had on average, 18.59; 9.03 and 9.38 mm in length; width and thickness, respectively. The dormancy was broken by immersion in cold water (8 ± 2 ° C) for 48 hours and germinating was conducted on vermiculite substrate. Article II – In the first, two experiments were carried out, the quality of the seeds collected in 2013, which have been stored for two years in cold and humid chamber was evaluated and sampled for TU testing, G% and sanity, and the second evaluated in the lot collected in 2015 the disinfestation of the seeds in the incidence of fungi and germination. Diaspores of B. riedelianum remained viable for 12 months under storage conditions, and disinfection with Orthocide® is indicated in order that provided high G% and IVG. The genus Aspergillus sp., Fusarium sp., Cladosporium sp. and Penicillium sp. were detected in both experiments. Article III - identified water depth required to optimize the growth of seedlings of B. riedelianum, and evaluated its initial field growth. Combinations were used of heads between 4, 8 and 12 mm day-1, after 180 days of water management application survival evaluation were performed, height, stem diameter, dry mass air, root dry weight and quality index Dickson. The treatments described in the vivarium were conducted in the field, wich 450 days after plantating were evaluated in relation to H, DC, MSA, leaf area and root length, chlorophyll content and chlorophyll a fluorescence. The head influenced the growth of seedlings of B. riedelianum, in the vivarium stage, which was confirmed in the field. Seedlings of Balfourodendron riedelianum can be produced initially with water depth of 4 mm day-1, which must be switched to 12 mm day -1after 60 days and remain so until the end of production.